2010
DOI: 10.1002/ejoc.201000959
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Cu‐Catalyzed Direct Alkenylation of Azole Heterocycles with Alkenyl Halides

Abstract: Direct alkenylation of azole heterocycles through Pd–Cu‐catalyzed C–H bond activation has been reported using alkenyl bromides as the coupling partners. The reaction enables the introduction of various mono‐, di‐, or trisubstituted alkenyl bromides as well as a benzyl chloride to the caffeine core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In pursuit of our efforts to extend further the scope of the functionalization of heteroaromatics through C–H bond activation, combined with our interest in discovering new hsp90 inhibitors,22,23 we have developed highly efficient and versatile Pd/Cu‐catalyzed C–H alkenylation reactions of a wide range of azoles. A catalyst system composed of Pd(acac) 2 /CuI/P( o ‐tolyl) 3 in THF in the presence of t BuOLi enables high‐yielding reactions with heterocycles, including the xanthines 28 , the adenines 26 , benzimidazoles, benzoxazoles, benzothiazoles, and thiazoles (Scheme ) 24. The substrate scope of the reaction turned out to be very broad, in terms not only of the azoles but also of a variety of mono‐, di‐, or trisubstituted alkenyl bromides.…”
Section: Direct Intermolecular Alkenylationmentioning
confidence: 99%
“…In pursuit of our efforts to extend further the scope of the functionalization of heteroaromatics through C–H bond activation, combined with our interest in discovering new hsp90 inhibitors,22,23 we have developed highly efficient and versatile Pd/Cu‐catalyzed C–H alkenylation reactions of a wide range of azoles. A catalyst system composed of Pd(acac) 2 /CuI/P( o ‐tolyl) 3 in THF in the presence of t BuOLi enables high‐yielding reactions with heterocycles, including the xanthines 28 , the adenines 26 , benzimidazoles, benzoxazoles, benzothiazoles, and thiazoles (Scheme ) 24. The substrate scope of the reaction turned out to be very broad, in terms not only of the azoles but also of a variety of mono‐, di‐, or trisubstituted alkenyl bromides.…”
Section: Direct Intermolecular Alkenylationmentioning
confidence: 99%
“…For example, C8 arylation reactions of xanthines with aryl halides have been conducted using CuI 6 or Pd(acac) 2 /CuI, 7 and C–H/C–H cross-coupling of xanthines has been accomplished using Pd(OAc) 2 /Cu(OAc) 2 . 8 N9-alkyl adenine derivatives have been subjected to C8 arylation reactions with aryl halides using Pd(OH) 2 /CuI.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous Pd/Cu-mediated C8 alkenylations of 6-(benzylthio)-9- N -benzylpurines with styryl bromides provided access to 6,8,9-trisubstituted purines [45]. The optimized conditions (Pd/CuI/ t BuOLi) were applicable for the selective alkenylation of caffeine, benzimidazole and other aromatic azole heterocycles [45,46]. These are significant developments since it was reported that 8-bromoadenosine was not a good substrate for Mizoroki-Heck reaction [47] making modification at 8 position via direct functionalization of C8-H bond a desirable transformation.…”
Section: Direct Activation Of C8-h Bond In Purine and Purine Nuclementioning
confidence: 99%